1099. Antibiotic Prescriptions for Acute Gastroenteritis during Office and Emergency Department Visits–United States, 2006–2015. (26th November 2018) - Collins, Jennifer P; Watkins, Louise Francois; King, Laura M; Bartoces, Monina; Fleming-Dutra, Katherine; Friedman, Cindy
Abstract: Background: Acute gastroenteritis (AGE) is a major cause of office and emergency department (ED) visits in the United States. Most patients can be managed with supportive care alone, although some require antibiotics. Limiting unnecessary antibiotic use can minimize side effects and the development of resistance. We used national data to assess antibiotic prescribing for AGE to target areas for stewardship efforts. Methods: We used the 2006–2015 National Hospital Ambulatory Medical Care Survey of EDs and National Ambulatory Medical Care Survey to describe antibiotic prescribing for AGE. An AGE visit was defined as one with a new problem (<3 months) as the main visit indication and an ICD-9 code for bacterial or viral gastrointestinal infection or AGE symptoms (nausea, vomiting, and/or diarrhea). We excluded visits with ICD-9 codes for Clostridium difficile or an infection usually requiring antibiotics (e.g., pneumonia). We calculated national annual percentage estimates based on weights of sampled visits and used an α level of 0.01, recommended for these data. Results: Of the 12, 191 sampled AGE visits, 13% (99% CI: 11–15%) resulted in antibiotic prescriptions, equating to an estimated 1.3 million AGE visits with antibiotic prescriptions annually. Antibiotics were more likely to be prescribed in office AGE visits (16%, 99% CI: 12–20%) compared with ED AGE visits (11%, 99% CI: 9–12%; P < 0.01). Among AGE visits with antibiotic prescriptions, the most frequently prescribed were fluoroquinolones (29%, 99% CI: 21–36%), metronidazole (18%, 99% CI: 13–24%), and penicillins (18%, 99% CI: 11–24%). Antibiotics were prescribed for 25% (99% CI: 8–42%) of visits for bacterial AGE, 16% (99% CI: 12–21%) for diarrhea without nausea or vomiting, and 11% (99% CI: 8–15%) for nausea, vomiting, or both without diarrhea. Among AGE visits with fever (T ≥ 100.9 o F) at the visit, 21% (99% CI: 11–31%) resulted in antibiotic prescriptions. Conclusion: Patients treated for AGE in office settings were significantly more likely to receive prescriptions for antibiotics compared with those seen in an ED, despite likely lower acuity. Antibiotic prescribing was also high for visits for nausea or vomiting, conditions that usually do not require antibiotics. Antimicrobial stewardship for AGE is needed, especially in office settings. Disclosures: All authors: No reported disclosures.